Creative Thinking Ability based on Students’ Metacognition in Creative Problem Solving Learning Model With Recitation and Self-Assessment in Ethnomatematics - Kusuma, Dani; Kartono, Kartono; Zaenuri, Zaenuri (Unnes Journal of Mathematics Education Research, 2019)
This research is aimed to (1) investigate the learning quality of the implementation of Creative Problem Solving model with recitation and self-assessment based on Ethnomatematics in students’ creative thinking ability; and (2) explain the creative thinking ability on Creative Problem solving model with recitation and Creative Problem Solving model with recitation and self-assessment based on Ethnomatematics in students’ metacognition. Mixed method with Sequential explanatory was applied in this research. The subject of the research was determined by students’ metacognition scores in VII C class in SMP N 1 Getasan academic year 2017/2018. Observation, test and interview were employed in obtaining the data. The data analysis appeared to prove that (1) Creative Problem Solving learning model with recitation and self-assessment based on Ethnomatematics has good quality in the stage of planning, learning process, and the final result of learning; (2) low metacognition subjects were able to fulfill the fluency an elaboration indicators, but flexibility indicator, novelty indicator and elaboration indicator had not been fulfilled yet; then moderate metacognition subjects were able to fulfill fluency indicator and elaboration indicator but the flexibility indicator and novelty indicator had not been fulfilled yet, high metacognition subjects were able to fulfilled the whole indicators includes fluency indicator, flexibility indicator, novelty indicator and elaboration indicator.